KONSEP PENGUKURAN DAN EVALUASI KINERJA - Mukrim Ainullah; Sanniati Muddin; Mardyawati (Jurnal Riset Multidisiplin Edukasi, 2025)
Performance measurement and evaluation are essential components of modern organizational management that function to assess effectiveness, efficiency, accountability, and the achievement of strategic objectives. This article aims to conceptually examine the approaches, indicators, challenges, and practices in performance measurement and evaluation based on a literature review of the last ten years from various national sources. Using a literature study method, the findings reveal that performance evaluation approaches have shifted from output-oriented models to those focused on outcomes and impacts, utilizing frameworks such as the balanced scorecard, result-based management (RBM), and key performance indicators (KPIs). Although information technology has significantly strengthened evaluation systems, several challenges remain, including limited human resource competencies, irrelevant indicators, and organizational cultures that do not support transparency. Therefore, alignment between strategic planning, indicator development, human resource capacity building, and the use of evidence-based information systems is necessary to establish an effective and sustainable performance evaluation system.